Takayasu's aorto-arteritis: Not your regular lesion for angioplasty - Navdeep Singh; Vivek Athwani; Vikas Bansal; Shaveta Kundra (Wolters Kluwer Medknow Publications, 2018)
We report a case of a 6-year-old female child with Takayasu's aorto-arteritis (TA) with severe coarctation of the aorta which resulted in an aortic dissection post-ballooning. This happened despite ensuring that markers for disease activity were negative, with appropriate corticosteroid therapy started before the procedure, and using a low-profile, low-pressure, and slightly undersized balloon for dilating the stenotic segment. It required immediate endovascular stenting to tide over the crisis. Following the procedure, she became normotensive with well-palpable lower limb pulses.